2008
DOI: 10.1002/ange.200800357
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic Nanoparticles as a Powerful Systems Biology Characterization Tool in the Physiological Context

Abstract: Superparamagnetische Eisenoxid‐Nanopartikel (SPIONs), die mit einem mitochondrial targetierenden Peptid (MTP), einem cyclischen RGD‐Peptid (cRGD) für die Zellinternalisierung und einem Fluorophor ausgestattet sind, können Mitochondrien sondieren. Nach magnetischer Isolierung aus den Zellen werden 48 Proteine massenspektrometrisch identifiziert, die mit den MTP‐cRGD‐SPIONs in einem Netzwerk aus 308 Wechselwirkungen interagieren (siehe Bild).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Interestingly, another study has shown that the improvement of in vitro cellular uptake of larger carboxy-dextran-coated SPIOs is rather due to surface properties than particle size, which may have large impacts on monocyte phagocytosis [31]. Studies have also shown that cationic surfaces facilitate cellular internalization [43, 44]. Accordingly, polycationic protamine sulfate was reported to bind on the dextran coating of iron oxide particles and modify the distribution of positive and negative surface charges, making these particles easily adhere to the cell membrane and facilitating uptake by the cell [45].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, another study has shown that the improvement of in vitro cellular uptake of larger carboxy-dextran-coated SPIOs is rather due to surface properties than particle size, which may have large impacts on monocyte phagocytosis [31]. Studies have also shown that cationic surfaces facilitate cellular internalization [43, 44]. Accordingly, polycationic protamine sulfate was reported to bind on the dextran coating of iron oxide particles and modify the distribution of positive and negative surface charges, making these particles easily adhere to the cell membrane and facilitating uptake by the cell [45].…”
Section: Discussionmentioning
confidence: 99%
“…A novel way of synthesizing and functionalizing ultrasmall Fe 3 O 4 NPs as contrast agents for in vivo tumor detection using MRI was presented by Chen and Sun [152], which was based on Mannich ligation between the iron chelated cathecol unit (157) and the -amino group of the lysine within the c(RGDyK) integrin binder. The schematic illustration of this chemistry is shown in Scheme 9.…”
Section: Optical and Magnetic Resonance Imagingmentioning
confidence: 99%
“…A superparamagnetic iron oxide nanoparticle-based (SPION) probe for dual-modality magnetic biology characterization/imaging with dual-targeting capability, was recently introduced by Petri-Fink et al [157] by exploiting the polyvalent nature of a SPION corona. To this purpose, the APS-coated SPIONs (APS = aminopropyltriethoxysilane) were manufactured by appending a fluorescent 7-hydroxycoumarin label, a mitochondrial targeting 22-mer peptide (MTP), and a v 3 -targeting c(RGDfK) moiety.…”
Section: Multimodal Display Systemsmentioning
confidence: 99%
“…A magnetic separation technique and the magnetic properties of SPIONs are useful to overcome these problems. Moreover, this technique creates the precise gradient removal of the NP-attached protein coronas3536. Thus, this study aims to probe the corona compositions of two important types of polymers (dextran and polyvinyl alcohol; PVA) with various surface charges using a magnetic separation method.…”
mentioning
confidence: 99%